2021
DOI: 10.1002/jcsm.12842
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relationship between intramuscular adipose tissue of the quadriceps and activities of daily living in older inpatients

Abstract: Background The longitudinal relationship between intramuscular adipose tissue of the quadriceps and activities of daily living (ADL) in older inpatients remains unclear. This study aimed to examine whether decrease of intramuscular adipose tissue of the quadriceps in older inpatients is related to the recovery of ADL than increase of muscle mass. Methods This longitudinal study included 202 inpatients aged ≥65 years [median age: 83.0 (77.0–88.0), 56.4% female]. Recovery of ADL during hospital stay was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…In future studies, US should be used to assess muscle quality, as recently reported Akazawa et al, who used US to measure muscle echo intensity to assess muscle quality. 26) Muscle quality should be evaluated together with muscle thickness and their impact on physical function and functional prognosis should be investigated in the future. Third, this study was conducted using a portable US device and cannot be generalized to all US devices.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, US should be used to assess muscle quality, as recently reported Akazawa et al, who used US to measure muscle echo intensity to assess muscle quality. 26) Muscle quality should be evaluated together with muscle thickness and their impact on physical function and functional prognosis should be investigated in the future. Third, this study was conducted using a portable US device and cannot be generalized to all US devices.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, appendicular skeletal muscle mass is related to knee extension strength [ 44 , 45 ], gait ability [ 46 ], and ADL [ 47 , 48 ]. However, intramuscular adipose tissue in the quadriceps shows increased association with knee extension strength [ 25 27 ], gait ability [ 28 30 ], and ADL [ 31 , 32 ] as compared to muscle mass. These findings indicate that in contrast to muscle mass, intramuscular adipose tissue of the quadriceps is indirectly related to swallowing ability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effects of aging and disuse are remarkably observed in the quadriceps of the upper and lower extremity muscles [ 63 , 64 ]. Furthermore, intramuscular adipose tissue in the quadriceps of older inpatients has been reported to be related to gait ability [ 28 30 ], ADL [ 31 , 32 ], and the onset of hospital-associated complications [ 65 ]. Based on these findings, targeting the quadriceps was considered valid in this study.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the intramuscular adipose tissue is more strongly associated with decreased muscle strength [ 7 , 8 ] and gait ability [ 9 ] and increased mortality [ 10 , 11 ] than the loss of muscle mass. Additionally, an increase in the intramuscular adipose tissue of the quadriceps of older patients decreases ADL [ 12 14 ] and the swallowing ability [ 15 ] and is related to hospital-associated complications [ 16 ] more so than the loss of muscle mass. Therefore, an increase in the intramuscular adipose tissue of the quadriceps is considered a severe problem for older individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study [ 18 ] reported that the decrease in ADL among patients with aspiration pneumonia is remarkable and that improving ADL among these patients is difficult. Because increased intramuscular adipose tissue of the quadriceps of older patients negatively affects ADL recovery more so than the loss of muscle mass [ 12 14 ], it is considered strongly related to ADL recovery among such patients. However, whether intramuscular adipose tissue of the quadriceps of older patients with aspiration pneumonia is related to ADL recovery after hospitalization remains unclear.…”
Section: Introductionmentioning
confidence: 99%